2015
DOI: 10.1007/s10654-015-0045-2
|View full text |Cite
|
Sign up to set email alerts
|

Size at birth and risk of breast cancer: update from a prospective population-based study

Abstract: Birth size variables (birth weight, birth length and head circumference) have been reported to be positively associated with adult breast cancer risk, whereas a possible association of placental weight has not been adequately studied. It has also been suggested that maternal height may modify the association of birth size with adult breast cancer risk, but this has not been studied in detail. We updated a long-term follow-up of 22,931 Norwegian women (average of 51 years of follow up during which 870 women wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…In contrast to the hypothesis that elevated levels of estrogen during pregnancy may be related to breast cancer in late life, we did not observe association between high birth weight and risk of postmenopausal breast cancer. Most previous studies reported that high birth weight was associated with increased risk for breast cancer among premenopausal women, while findings for postmenopausal breast cancer risk have been inconsistent . Findings for postmenopausal breast cancer ranged from a significant positive association to a significant inverse association with most of studies showing no significant association .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast to the hypothesis that elevated levels of estrogen during pregnancy may be related to breast cancer in late life, we did not observe association between high birth weight and risk of postmenopausal breast cancer. Most previous studies reported that high birth weight was associated with increased risk for breast cancer among premenopausal women, while findings for postmenopausal breast cancer risk have been inconsistent . Findings for postmenopausal breast cancer ranged from a significant positive association to a significant inverse association with most of studies showing no significant association .…”
Section: Discussionmentioning
confidence: 97%
“…Most previous studies reported that high birth weight was associated with increased risk for breast cancer among premenopausal women, while findings for postmenopausal breast cancer risk have been inconsistent . Findings for postmenopausal breast cancer ranged from a significant positive association to a significant inverse association with most of studies showing no significant association . It is worthy to note that a recent study of the association between weight at birth and breast cancer risk (combined premenopausal and postmenopausal cases) using a Mendelian randomization approach also reported that genetically predicted higher birth weight was not associated with an increased risk of breast cancer in adult life, and the association was robust even after controlling for estrogen receptor status …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The neonatal birth size is a well-established risk factor for breast cancer. Studies during the last two decades, from several countries, have consistently shown that birth weight and birth length positively correlate with breast cancer in women <50 years old [ 57 63 ]. Bigger babies have larger mammary glands and the number of mammary stem cells is proportional to its size [ 64 66 ].…”
Section: Birth Size and Breast Cancermentioning
confidence: 99%
“…It can, thus, be inferred that among taller mothers, maternal size does not impose constraints on fetal growth, thus allowing growth-enhancing pregnancy hormones to exercise their growth potential and be positively associated with birth size and, thus, the risk of breast cancer [6]. In 2015, Vatten and colleagues studied a cohort of women in Norway and reported a positive association of birth length with breast cancer risk, which was stronger among women whose mothers were relatively tall (median or taller) compared to women whose mothers were relatively short (below median) at childbearing [10]. The results of the Norwegian cohort are in line with the results reported in our study in supporting a role of maternal height in breast cancer aetiology.…”
mentioning
confidence: 99%